The Influence Of The Compliance Of Anti Hypertension Diet On Lowering Blood Pressure In Elderly - Salmia (Chakra Brahmanda Lentera Institute, 2020)
Hypertension is a problem that is difficult to control because people with hypertension rarely feel a symptom that the patient unconsciously experiences complications in vital organs such as the brain and kidney. Prevention of hypertension can be done with a hypertensive diet in a sustainable manner to prevent further severe effects. Objective To find out whether there is a Hypertension Diet Compliance with Blood Pressure in the Elderly in Muara Besar Village Ogodeide Public Health Center Tolitoli District.. The design used in the study is correlational analytic population are all elderly hypertension. The sample size is 37 respondents using the Simple Random sampling technique. Independent variable of research is diet compliance. The dependent variable is blood pressure. Data was collected using a questionnaire, then the data were analyzed using the Spearman rho test, with a significance level of α < 0.05. The results showed that p = 0.021 with a = 0.05, which means that H0 was rejected and H1 was accepted so that it could mean that there was a relationship between adherence to the anti-hypertensive diet to blood pressure reduction in the elderly in Muara Besar Village Ogodeide Community Health Center Tolitoli District, with a correlation coefficient 0.379 which means having a strong enough relationship. An appropriate hypertension diet can help reduce blood pressure by reducing the consumption of causes that cause high blood pressure